Companion animal organoid technology to advance veterinary regenerative medicine - Penning, Louis C.; van den Boom, Robin (Frontiers in Veterinary Science, 2023)
First year medical and veterinary students are made very aware that drugs can have very different effects in various species or even in breeds of one specific species. On the other hand, the “One Medicine” concept implies that therapeutic and technical approaches are exchangeable between man and animals. These opposing views on the (dis)similarities between human and veterinary medicine are magnified in regenerative medicine. Regenerative medicine promises to stimulate the body’s own regenerative capacity via activation of stem cells and/or the application of instructive biomaterials. Although the potential is enormous, so are the hurdles that need to be tackled before large scale clinical implementation. It is in the advancement of regenerative medicine that veterinary regenerative medicine can play an instrumental and crucial role. This review describes the discovery of (adult) stem cells in domesticated animals, mainly cats and dogs. The promise of cell-mediated regenerative veterinary medicine is compared to the actual achievements, and this will lead to a set of unanswered questions (controversies, research gaps, potential developments in relation to fundamental, pre-clinical and clinical research). For veterinary regenerative medicine to have impact, answering these questions is pivotal.